Workers Self-Management (AmeriQuests, 2016)
Introduction to Lawrence B. Cohen's "Workers and Decision Making on Production" (1949), a case study of worker-management decision-making in a textile (carpet) factory in Connecticut
Keywords: workers' self-management; decision-making; shop floor; management; unions; factory production